2016
DOI: 10.1111/jocn.13215
|View full text |Cite
|
Sign up to set email alerts
|

Teaching menstrual care skills to intellectually disabled female students

Abstract: To achieve improved success in life, it is important that adolescents assume the responsibility of self-care and manage sustained care activity on their own.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
52
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 20 publications
0
52
0
1
Order By: Relevance
“…Five studies (23%) investigated MHM training given to people with intellectual impairments [35, 37, 43, 46, 47]. One study highlighted a lack of training and support provided to this group because carers did not believe that the individual would understand MHM information [35].…”
Section: Resultsmentioning
confidence: 99%
“…Five studies (23%) investigated MHM training given to people with intellectual impairments [35, 37, 43, 46, 47]. One study highlighted a lack of training and support provided to this group because carers did not believe that the individual would understand MHM information [35].…”
Section: Resultsmentioning
confidence: 99%
“…More than half of participants in the present study reported intellectual impairment; previous research indicates that with support women with intellectual impairment(s) and/or high support needs can understand and accept their menstruation [2,23] however, this is best achieved via the provision of menstrual education in the years leading up to menarche allowing time for knowledge acquisition and practice [12], and if the teaching tools and approaches are adapted to meet participants specific learning needs [31]. Menstrual interventions in Bangladesh for young adolescent women with CP and their mothers need to address these considerations and the conflicting requirement of menarche as a pathway to knowledge, as well as be physically, financially and socially accessible and inclusive.…”
Section: Discussionmentioning
confidence: 63%
“…It was thought that these positive improvements in the habits of the teenagers might be derived from the activities within the training program designed for menstrual hygiene. Other studies have shown that training given to teenagers with ID positively affected their hygiene habits during the menstrual period (Altundag & Calbayram, ; Epps, Stern, & Horner, ; Kuloglu‐Aksaz & Firat, ; Richman, Ponticas, Page, & Epps, ).…”
Section: Discussionmentioning
confidence: 96%
“…In some cultures, there are false (superstitious) beliefs such as considering women dirty during menstruation and isolating them from society. Other such beliefs include considering swimming, taking a shower, having dental treatment, and doing exercises as harmful and thinking that women lose too much blood by changing hygienic pads (Altundag & Calbayram, ; Atabey & Nazbak, ; Sakar, Ozkan, Sarac, Atabey, & Nazbak, ). Emergence of such behaviors might also be influenced by the environment in which the teenagers were living, the family situation, and educational status of their parents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation